A Combined Molecular Dynamic Simulation and Synchrotron X‐Ray Absorption Spectroscopy to Characterize the Atomistic Local Structure of Ion‐Containing Polymers. Issue 1 (13th April 2023) - Vao‐soongnern, Visit; Chaodamrongsakul, Jittima; Reungsri, Kanokporn; Sirirak, Kanjana; Amonpattaratkit, Penphitcha; Klysubun, Wantana
Abstract: A combined method of molecular dynamic (MD) simulation and synchrotron extended X‐ray absorption fine structure (EXAFS) spectroscopy has been applied to characterize the atomistic local structure of salt ion in polypropylene glycol/potassium thiocyanate (PPG/KSCN). Agreement between simulated and experimental EXAFS spectra is satisfied for both amplitude and frequency. Results imply that, by average, K + ions are coordinated with PPG by 3.8 ether oxygen at the distance of 2.65 Å from two PPG chains. K + ions are coordinated to one thiocyanate (SCN − ) ion at both N and S position. Polymer chains have more gauche conformation in PPG/KSCN compared to neat PPG.